Anticancer effects of alpelisib on PIK3CA-mutated canine mammary tumor cell lines - Yeom, Jiah; Cho, Yoonju; Ahn, Seoungyob; Jeung, Soyoung (Frontiers in Veterinary Science, 2023)
Canine mammary tumors (CMTs) are commonly observed in old and unspayed female dogs. Recently, dogs have been increasingly spaying at a young age to prevent mammary tumors. These CMTs require extensive local excision and exhibit a high probability of metastasis to the regional lymph nodes and lungs during malignancy. However, the molecular and biological mechanisms underlying CMT development have not been fully elucidated, and research in this area is limited. Therefore, in this study, we established new CMT cell lines by isolating cells from tumor tissues and investigated phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA), a target for human breast cancer. PIK3CA mutations were observed at a similar loci as in the human PIK3CA gene in half of all canine samples. Furthermore, we investigated whether alpelisib, a PIK3CA inhibitor approved by the U.S. Food and Drug Administration for human breast cancer treatment, along with fulvestrant, is effective for CMT treatment. Alpelisib exerted stronger anticancer effects on cell lines with PIK3CA mutations than on the wild-type cell lines. In conclusion, we established new CMT cell lines with PIK3CA mutations and confirmed the efficacy of alpelisib for CMT treatment in vitro.